Lead concentration in skeletal muscle in amyotrophic lateral sclerosis patients and control subjects. Issue 11 (November 1978) - Conradi, S; Ronnevi, L O; Vesterberg, O
Abstract : The concentration of lead in the vastus lateralis muscle was determined in patients with amyotrophic lateral sclerosis and control subjects by flameless atomic absorption spectrophotometry. No statistically significant differences were found between these groups, and in both the figures were of the same magnitude as those earlier reported for normal individuals. Increased plasma lead concentrations do not seem to cause a significant deposition of lead in skeletal muscle. Therefore, plasma rather than skeletal muscle is the more likely source if pathological amounts of lead enter the motoneurones via the retrograde axoplasmic flow in amyotrophic lateral sclerosis.